The effect of rheology with gas bubbles on linear elastic waves in fluid-saturated granular media - Ali, Adham; Strunin, Dmitry (Zielona Góra: Uniwersytet Zielonogórski)
Elastic waves in fluid-saturated granular media depend on the grain rheology, which can be complicated by the presence of gas bubbles. We investigated the effect of the bubble dynamics and their role in rheological scheme, on the linear Frenkel-Biot waves of P1 type. For the wave with the bubbles the scheme consists of three segments representing the solid continuum, fluid continuum and bubbles surrounded by the fluid. We derived the Nikolaevskiy-type equation describing the velocity of the solid matrix in the moving reference system.
Keywords: Frenkel-Biots waves; bubbles; rheology; porous media